Randomized Trial Comparing Two Mass Casualty Triage Systems (JumpSTART versus SALT) in a Pediatric Simulated Mass Casualty Event. (3rd July 2014) - Jones, Nicole; White, Marjorie Lee; Tofil, Nancy; Pickens, MeKeisha; Youngblood, Amber; Zinkan, Lynn; Baker, Mark D.
Abstract Purpose. Several field triage systems have been developed to rapidly sort patients following a mass casualty incident (MCI). JumpSTART (Simple Triage and Rapid Transport) is a pediatric-specific MCI triage system. SALT (Sort, Assess, Lifesaving interventions, Treat/Transport) has been proposed as a new national standard for MCI triage for both adult and pediatric patients, but it has not been tested in a pediatric population. This pilot study hypothesizes that SALT is at least as good as JumpSTART in triage accuracy, speed, and ease of use in a simulated pediatric MCI. Methods. Paramedics were invited and randomly assigned to either SALT or JumpSTART study groups. Following randomization, subjects viewed a 15-minute PowerPoint lecture on either JumpSTART or SALT. Subjects were provided with a triage algorithm card for reference and were asked to assign triage categories to 10 pediatric patients in a simulated building collapse. The scenario consisted of 4 children in moulage and 6 high-fidelity pediatric simulators. Injuries and triage categories were based on a previously published MCI scenario. One investigator followed each subject to record time and triage assignment. All subjects completed a post-test survey and structured interview following the simulated disaster. Results. Forty-three paramedics were enrolled. Seventeen were assigned to the SALT group with an overall triage accuracy of 66% ±15%, an overtriage mean rate of 22 ± 16%, and an undertriage rate of 10 ± 9%. Twenty-six participants were assigned to the JumpSTART group with an overall accuracy of 66 ± 12%, an overtriage mean of 23 ±16%, and an undertriage rate of 11.2 ± 11%. Ease of use was not statistically different between the two systems (median Likert value of both systems = 2, p = 0.39) Time to triage per patient was statistically faster in the JumpSTART group (SALT = 34 ± 23 seconds, JumpSTART = 26 ± 19 seconds, p = 0.02). Both systems were prone to cognitive and affective error. Conclusion. SALT appears to be at least as good as JumpSTART in overall triage accuracy, overtriage, or undertriage rates in a simulated pediatric MCI. Both systems were considered easy to use. However, JumpSTART was 8 seconds faster per patient in time taken to assign triage designations. Key words: mass casualty triage; pediatric; simulation